2014
DOI: 10.1371/journal.pone.0113701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Intravitreal Injection of Aflibercept and Ranibizumab on Glomeruli of Monkeys

Abstract: PurposeIt is known that endothelial cells in the kidney are also strongly VEGF-dependent. Whether intravitreal drugs can be detected within the glomeruli or affect VEGF in glomerular podocytes is not known. Therefore, the aim of this pilot study was to investigate the effects of a single intravitreal injection of aflibercept and ranibizumab on glomeruli of monkeys.MethodsThe kidneys of eight cynomolgus monkeys, which were intravitreally injected either with 2 mg of aflibercept or with 0.5 mg of ranibizumab, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
27
2
Order By: Relevance
“…We found reduced VEGF and CFH levels in murine kidneys 48 hours after intravitreal injection. This confirmed primate studies that detected anti-VEGF agents in glomeruli one day after intravitreal injection (74). Furthermore, glomerular dysfunction has been reported for all intravitreal VEGF antagonists currently used in patients (75, 76).…”
Section: Discussionsupporting
confidence: 86%
“…We found reduced VEGF and CFH levels in murine kidneys 48 hours after intravitreal injection. This confirmed primate studies that detected anti-VEGF agents in glomeruli one day after intravitreal injection (74). Furthermore, glomerular dysfunction has been reported for all intravitreal VEGF antagonists currently used in patients (75, 76).…”
Section: Discussionsupporting
confidence: 86%
“…In vitro studies have reported that VEGF in the kidney, which was highly expressed by the podocytes and activates VEGF receptor 2 on glomerular capillary endothelial cells, plays an important role in maintaining normal glomerular structure and function, and its inhibition might be associated with endothelial dysfunction and podocyte dysregulation [2][3][4][5]12 . The doses of the intravitreously administered VEGF inhibitors in the present study were much lower than those administered intravenously 13 ; however, aflibercept and ranibizumab could be detected in the glomerular capillaries in monkeys after one intravitreal injection 14 . In addition, a few cases of AKI events after intravitreal anti-VEGF therapy have been reported, although we were unable to explain the differences observed between the current study and the AKI cases 7,8 .…”
Section: Discussioncontrasting
confidence: 54%
“…1,2,8 That is not all, as VEGF blockade can also induce changes in pro-thrombotic pathways (Diacyl-glycerol (DAG)-Kinase epsilon), in addition it affects nitric oxide signaling. 2,8 These are very well documented for systemic anti-VEGF toxicity and increasingly being shown in patients receiving intravitreal VEGF injections which are now known to be systemically absorbed according to Avery et al 3,9 An additional study by Tschulakow et al 10 also shows that not all VEGF blocking agents present the same risk. He shows that ranibizumab is present for shorter periods of time at simian glomeruli than aflibercept, effects systemic VEGF less, and that ranibizumab does not induce changes in endothelial fenestrations of glomerular capillaries seen with longer acting anti-VEGF agents like aflibercept.…”
Section: Discussionmentioning
confidence: 99%